As transformações no mundo do trabalho : um estudo sobre a precarização e qualificação profissional dos operadores de telemarketing na cidade de Uberlândia, MG - Souza, Luciene Maria de (2007)
This research approaches the existent contradictions between the professional qualification and the precariousness of the telemarketing operators work in Uberlândia, Minas Gerais. It recovers the dialectic mediations between that process and the transformations in the work environment. In recent years the service sector presents a considerable growth in Brazil and particularly in Uberlândia. Though, that growth is materialized in a context of productive restructuring of the capital that has as consequences the flexibility, precariousness and fragmentation of the working class. Discussing on the principles of the dialectic historical materialism that has among its presuppositions the criticism of the work in the capitalist production mode, we demonstrate that unlike the optimistic discourses of the capital that point to the consolidation of workers endowed with larger intellectual content in the end of the twentieth century and beginning of the twenty-first century, we verified the permanence of work ways which are alienated and precarious. In that way, we approached the impacts of the structural crises of the monopolist capitalism that are present in the existent relationships between work and education facing the transformations of the productive process as well as its reflexes in the organization of the work and in the process of professional qualification of the telemarketing operators in the company researched in UberlândiaMG.